2008
DOI: 10.1002/mop.23654
|View full text |Cite
|
Sign up to set email alerts
|

Angle and polarization‐independent bandstop frequency selective surface for indoor wireless systems

Abstract: An UWB VCO with tunable active inductors using a 0.18-m CMOS standard process was presented in this article. The active inductors provide inductance from 1.7 to 3.6 nH with the qualityfactor Ͼ10 via a tunable feedback resistance. By utilizing the tunable active inductors in VCO design, the novel VCO exhibits oscillation frequencies from 2.16 to 6.16 GHz with a tuning-range of more than 100%. Comparisons of the proposed VCO with a conventional topology show that the proposed circuit achieves better performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Our prior research indicated that the cross-dipole FSS provides the required bandwidth and an acceptable angular stability [14], [15]. Therefore, it was chosen for FSS due to its simplicity and relatively better performance.…”
Section: Selection Of Fss Elementmentioning
confidence: 99%
“…Our prior research indicated that the cross-dipole FSS provides the required bandwidth and an acceptable angular stability [14], [15]. Therefore, it was chosen for FSS due to its simplicity and relatively better performance.…”
Section: Selection Of Fss Elementmentioning
confidence: 99%
“…Frequency Selective Surfaces are exhaustively studied in the literature [1,2] and implemented for gamut of applications especially in shielding [3][4][5][6][7]. The erstwhile contribution from FSS's designed for shielding GSM signals have their array elements as square [8,9] and ring geometries [9].…”
Section: Introductionmentioning
confidence: 99%
“…For some applications, especially at low frequency, FSS of relatively small electrical dimension is highly desirable. Furthermore, the explosive growth recently in wireless security [6][7][8] has also increased the demands for FSS miniaturization techniques. For wireless security in buildings, FSS may be placed in the walls of the building to provide isolation, reduce interference between adjacent vicinities and protect people from electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In [6][7][8][9][10], the oblique incidence and polarization performance of the cross dipole FSS, the bandwidth enhancement using SIW (substrate integrated waveguide), and the effect of the building materials on FSS response have been investigated. However, the size reduction is not satisfactory, and the manufacture cost is higher (the structure is more complex).…”
Section: Introductionmentioning
confidence: 99%